Employees' performance and organisational culture in the utility sector/ Nur Shafini Mohd Said ... [et al.] - Mohd Said, Nur Shafini; Yusof, Raghadah; Omar Ali, Siti Rapidah; Mat, Khalid Amin; Mansor, Farah Ahlami (Universiti Teknologi MARA, Perlis, 2022)
The study investigates the influence of organisational culture towards employee performance in the utility sector. There is a lack of cultural integration between employees, which is a primary cause of failure in the utility sector. The purpose of the study is to analyse the relationships between factors that influence employee performance, which are employee participation, openness to communication, and reward systems among the employees of the utility sector. The researchers have selected the employees working in the utility sector as the study's population, which has included 134 employees. A set of questionnaires has been used to collect and analyse data and distributed via Google Form to the respondents. The statistical analyses have been performed by using Version 23 of the Statistical Package for Social Science (SPSS). In order to identify the impact of organisational culture on the employees of this sector, Correlation analyses have been used. The results show that there is a strong relationship between independent and dependent variables. The results also indicate that the three hypotheses are accepted. The researchers hope that the results will also provide benefits to the organisation. As a result, the study focuses on how an effective organisational culture is formed to improve employee performance can be identified. Furthermore, this study has also emphasised the current theoretical and empirical gaps in the field of organisational culture and employee performance, hence, the findings may be valuable for future research.